Progress or Collapse. - De Vogli, Roberto (Taylor and Francis, 2012)
Human progress is heading toward collapse. There are converging ecological crises looming on the horizon: climate change, peak oil, water shortages, fish depletion and food scarcities. The world is on a collision course against the limits of the ecosystem. Modern societies are consuming, polluting and growing as if there is no tomorrow. Indeed, there may not be one. In Progress or Collapse, Roberto De Vogli guides us through the multiple converging global crises of economic progress. He explores the connections between the environmental crisis and the psychological, social, c.